Evaluation of the Implementation of the Independent Curriculum with a Technology-based Learning Model - Suryati, Lili; Ambiyar; Jalinus, Nizwardi (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The implementation of the independent Curriculum in the field of education through the utilization of technology models oriented towards Society 5.0 era, such as Internet of Things (IoT) or Artificial Intelligence (AI), big data, and artificial robots that will fulfill human needs to address other requirements. This research analyze three perspectives: students, teachers, and institutions related to implementation of the independent Curriculum oriented towards Society 5.0 era. This study uses a mixed method research approach. The data collection technique in this study used random sampling techniques. Data analysis is inductive or qualitative, and the results of this study emphasize meaning rather than generalization. From the student's perspective, there is a significant difference indicating a significant difference between the previous curriculum-13 and the implementation of the Merdeka Curriculum in terms of students' development at school. From the teacher's perspective, indicates a significant difference, meaning that access to relevant educational resources and participation in professional activities are evident. From the institution's perspective, 97.9% of schools and teachers have accessed the digital platform of the independent Curriculum, with only 2.02% remaining to implement it. The implementation of the Merdeka Curriculum allows schools, teachers, and students the freedom to organize and develop their own curriculum while encouraging the use of technology in learning.